Enhancing Early Prevention of Childhood Obesity in Primary Care: Cultural adaptation and validation of the Family Nutrition and Physical Activity tool in Portugal - Sónia B. R.; Rodrigues, R. B.; Luís, S.; Luisa Barros; Salantera S. (Prevention of Childhood Obesity: Body, Brain and Society, Novo Nordisk Foundation Science Cluster, 2026)
Background: Early childhood is a decisive period for shaping lifestyle behaviours associated with obesity risk, and primary care settings are well-positioned to support families. Yet, the absence of culturally validated tools in Portugal limits professionals’ ability to systematically identify obesogenic family environments. Objective: To translate and culturally adapt the Family Nutrition and Physical Activity tool (FNPA-PT) and assess its clarity, acceptability, and content validity among parents attending well-child visits. Methods: Following internationally recognised guidelines (Beaton; MAPI), the FNPA was translated and refined through a multi-step process. Cognitive interviews with parents of five-year-old children in a primary care centre, guided by Tourangeau’s response model, explored comprehension, retrieval, judgement, and response processes. Results: Semantic equivalence between translations was high (85% satisfactory or perfect). Parents reported strong comprehensibility and relevance of the FNPA-PT, highlighting its usefulness for ref lecting on routines related to diet, physical activity, screen use, and sleep. Minor adaptations improved cultural alignment. The tool was feasible during well-child visits and supported dialogue between families and health professionals. Conclusion: The FNPA-PT is a validated, culturally appropriate resource that strengthens early prevention efforts in Portuguese primary care. By enabling structured conversations about lifestyle behaviours, it promotes a more proactive and family-centred approach to childhood obesity prevention.